2021
DOI: 10.3390/ph14090888
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Target Actions of Acridones from Atalantia monophylla towards Alzheimer’s Pathogenesis and Their Pharmacokinetic Properties

Abstract: Ten acridones isolated from Atalantia monophylla were evaluated for effects on Alzheimer’s disease pathogenesis including antioxidant effects, acetylcholinesterase (AChE) inhibition, prevention of beta-amyloid (Aβ) aggregation and neuroprotection. To understand the mechanism, the type of AChE inhibition was investigated in vitro and binding interactions between acridones and AChE or Aβ were explored in silico. Drug-likeness and ADMET parameters were predicted in silico using SwissADME and pKCSM programs, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Drug-likeness is a useful concept in drug design that increases the chances of chemical entities and avoids drug development failure. In this study, the SwissADME web server ( , accessed on 30 December 2021) was performed to estimate the physicochemical features of anthraquinones 1 – 4 , to assess their drug-likeness [ 21 ]. The results ( Table 4 ) showed that 1 – 4 presented no violation of Lipinski’s rules.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-likeness is a useful concept in drug design that increases the chances of chemical entities and avoids drug development failure. In this study, the SwissADME web server ( , accessed on 30 December 2021) was performed to estimate the physicochemical features of anthraquinones 1 – 4 , to assess their drug-likeness [ 21 ]. The results ( Table 4 ) showed that 1 – 4 presented no violation of Lipinski’s rules.…”
Section: Resultsmentioning
confidence: 99%
“…Trp84, Phe330 and His440 were identical binding sites for both substrate (acetylcholine) and inhibitor (matrine, berberine or osthole). In previous papers, amino acids Trp84, Tyr130, Phe330 and Phe331 are responsible for the molecular recognition of quaternary ammonium ligands and also the catalytic anionic sites (Lee et al 2015;Takomthong et al 2021). Therefore, the three AHCs probably inhibit AchE through competitively occupation of the active catalytic channel.…”
Section: Ache Inhibition By Ahcsmentioning
confidence: 99%
“…In addition, they can promote several biological activities implicated in preventing cancer, chronic inflammation, cardiovascular disorders, and neurodegenerative disease [11][12][13][14]. Oxidative stress has been implicated in Alzheimer's disease (AD); memory impairment in AD patients is related to the decline in the acetylcholine (ACh) level in the cholinergic system [15]. Therefore, AChE inhibitors are used for stabilizing the ACh neurotransmitter levels in the synaptic cleft [15].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been implicated in Alzheimer's disease (AD); memory impairment in AD patients is related to the decline in the acetylcholine (ACh) level in the cholinergic system [15]. Therefore, AChE inhibitors are used for stabilizing the ACh neurotransmitter levels in the synaptic cleft [15]. On the other hand, a large number of halophyte plants have been traditionally used to reduce blood pressure (Salsola kali L., Chenopodiaceae), for the treatment of cancer (Artemisia scopariae Waldst.…”
Section: Introductionmentioning
confidence: 99%